2014
DOI: 10.2519/jospt.2014.4847
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Diagnostic Classification of Patients With Temporomandibular Disorders: Implications for Physical Therapists

Abstract: Researchers and expert clinicians in orofacial pain have long acknowledged the Differential DiagnosisIn addition to the musculoskeletal structures (TMJ and the masticatory muscles) and the psychological factors discussed, orofacial pain may result from or be exacerbated by (1) primary HAs (migraine, cluster, tension type, other primary); (2) secondary HAs related to systemic problems such as cardiovascular and rheumatoid disorders and disorders related to the cervical spine, ears, sinuses, eyes, medications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
1
25
0
4
Order By: Relevance
“…The same study suggested spinal and central hyperexcitability in TMD subjects. The central sensitisation process may amplify the pain information in the brain, resulting in a reduction in the normal central inhibitory mechanisms that help to balance activation of pain centres . The TMJ pain is an usual complaint in subjects with TMD, and it can be a referred pain from the myalgia due to central or even peripheral sensitisation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study suggested spinal and central hyperexcitability in TMD subjects. The central sensitisation process may amplify the pain information in the brain, resulting in a reduction in the normal central inhibitory mechanisms that help to balance activation of pain centres . The TMJ pain is an usual complaint in subjects with TMD, and it can be a referred pain from the myalgia due to central or even peripheral sensitisation .…”
Section: Discussionmentioning
confidence: 99%
“…The central sensitisation process may amplify the pain information in the brain, resulting in a reduction in the normal central inhibitory mechanisms that help to balance activation of pain centres. 40 The TMJ pain is an usual complaint in subjects with TMD, and it can be a referred pain from the myalgia due to central or even peripheral sensitisation. 23,41,42 The PPT increased overtime for both groups, but no differences were observed within or between groups anytime.…”
Section: Discussionmentioning
confidence: 99%
“…The current medical approach for treating people with TMD is to provide the least invasive medical care (Harrison et al, ; Okeson & de Leeuw, ). Physical therapy, including thoracic TJM, has been considered less invasive when compared with other interventions (Magoun, ).…”
Section: Discussionmentioning
confidence: 99%
“…The current medical approach for treating people with TMD is to provide the least invasive medical care (Harrison et al, 2014;Okeson & de Leeuw, 2011). Physical therapy, including thoracic TJM, has been considered less invasive when compared with other interventions (Magoun, 1976 Participants with TMD generally demonstrated reduced MMO, but the authors found no difference in MMO improvement between groups following TJM.…”
Section: Discussionmentioning
confidence: 99%
“…La ATM se caracteriza por ser una de las articulaciones más complejas del organismo; está clasificada como una diartrosis bicondílea, y es la única en todo el organismo constituida por dos articulaciones situadas entre el hueso mandibular y el temporal. Se caracteriza por ser una articulación sinovial, la cual contiene dos espacios articulares aislados por un disco fibrocartilaginoso 2,3 . Se especializa por trabajar conjuntamente con el lado opuesto, en forma sincrónica, se encuentra relacionada con la oclusión y el sistema neuromuscular, que actualmente se consideran contribuyentes en la remodelación y la adaptación de la ATM.…”
Section: Introductionunclassified